Deparpolisasi Keanggotaan Dewan Perwakilan Daerah (Tela'ah Atas Hasrat Partai Politik Dalam Mengokupasi DPD) - Kiki Wulandari; Putri Apriani; Zulkifly Zulkifly; Irfan Amir (Al-Adalah: Jurnal Hukum dan Politik Islam, 2020)
The beginning of filling the first period of DPD seats (2004-2009) required that the candidate for the DPD members were not an administrator of political parties within a minimum period of four years that calculated until the date of nominating candidates. However, along with the political power struggling in parliament, this requirement then removed in the requirements for the next period of DPD membership. The implication, after being elected as DPD members, the senators forget about their constituent and choose to join certain political parties, the impact of the DPD that they were not focus anymore to fight for the local aspirations of their region, in otherwise they tend to fight for the interests of their political groups/parties. To understand and examine above the problem, the authors conducted normative legal research, with two research approaches namely the statute approach and the conceptual approach. The results showed that the constitutionality of the nomination of DPD members from political parties is the desire of political parties to occupy the DPD which is it cannot be justified, with the following arguments; (i) deny the Original Intent of DPD formation, (ii) The concept of bicameralism requires that there are differences in ingredients between the DPR and DPD so that there is no double representation.